2017
DOI: 10.1016/j.jmarsys.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of urban effluents on summer hypoxia in the highly turbid Gironde Estuary, applying a 3D model coupling hydrodynamics, sediment transport and biogeochemical processes

Abstract: Estuaries are increasingly degraded due to coastal urban development and are prone to hypoxia problems. The macro-tidal Gironde Estuary is characterized by a highly concentrated turbidity maximum zone (TMZ). Field observations show that hypoxia occurs in summer in the TMZ at low river flow and a few days after the spring tide peak. In situ data highlight lower dissolved oxygen (DO) concentrations around the city of Bordeaux, located in the upper estuary. Interactions between multiple factors limit the understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 66 publications
(109 reference statements)
2
19
1
Order By: Relevance
“…We are also missing potentially important pollution sources in the form of big coastal cities delivering waste and rain water directly to the sea. Such point sources of pollution have been shown to greatly modify production seasonality and nutrients ratios (e.g., Romero et al ) and to contribute to bottom hypoxic conditions nearby the sewage areas (e.g., Lajaunie‐Salla et al ). We also lack the direct input of OM by the river waters, which, in reaching the bottom, could contribute to oxygen depletion.…”
Section: Discussionmentioning
confidence: 99%
“…We are also missing potentially important pollution sources in the form of big coastal cities delivering waste and rain water directly to the sea. Such point sources of pollution have been shown to greatly modify production seasonality and nutrients ratios (e.g., Romero et al ) and to contribute to bottom hypoxic conditions nearby the sewage areas (e.g., Lajaunie‐Salla et al ). We also lack the direct input of OM by the river waters, which, in reaching the bottom, could contribute to oxygen depletion.…”
Section: Discussionmentioning
confidence: 99%
“…To account for the influence of salinity on flocculation, a dependency between the mud settling velocity and salinity ( S ) was computed (Migniot, 1968; Mikes et al, 2004; Thill et al, 2001). This effect was previously accounted for by Lajaunie‐Salla et al (2017) in the Gironde estuarine system and largely contributed to simulate high SSC levels and maintain the ETM in the tidal rivers. A critical salinity S cr of 5 psu was chosen, below which settling velocity decreases with salinity, as follows: ws,italicmud={ws,italicmud0,0.5emitalicif0.25emSScrmax)(,ws,minS*ws,mud0Scr,0.5emitalicif0.25emS<Scr. …”
Section: Methodsmentioning
confidence: 79%
“…They showed that the area exhibiting hypoxia was greatly affected by wind speed and direction, but was insensitive to river discharge. Lajaunie-Salla et al [13] also applied a modeling method to assess the impact of urban wastewater treatment plants (WWTPs) and sewage overflows (SOs) on hypoxia in the Gironde Estuary, France. The modeling results revealed that particulate organic carbon (POC) from urban waste was resuspended during the spring tide, thereby expanding the hypoxia area.…”
Section: Introductionmentioning
confidence: 99%
“…Those researchers also found that hypoxic events could be mitigated by blocking the POC from the WWTPs and SOs. Overall, the findings to date can be summarized as follows: DO depletion of an estuarine area is mainly caused by excessive nutrients and organic matter, and the formation of a hypoxia zone is closely related to deteriorated circulation due to stratification and upstream freshwater inflow [10][11][12][13][14][15][16][17][18]. In addition, the spatial distribution of hypoxia in a small estuarine area is affected by river inflow [10,11,13], while that in a large estuarine area is influenced by wind [12,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation